(untitled) (Third Sector Social Economic Review, 2025)
This study aims to evaluate operational and environmental efficiency in the pharmaceutical sector, which is crucial in economic and social terms but also has known negative effects on the environment. Operational and environmental performance indicators obtained from the sustainability and activity reports of local and international pharmaceutical companies through document scanning were analyzed with the variable returns to scale (VRS) model of Data Envelopment Analysis (DEA). A multiplicative inverse transformation approach was used for undesirable input and output variables in DEA. According to the findings, the operational and environmental efficiency rankings of the companies differ. While Abbivie, Johnson&Johnson and Merck & Co. companies, which are effective in terms of operational performance, have a very low environmental efficiency level; Biogen and Regeneron Pharm. companies also have a higher environmental efficiency ranking compared to their operational efficiency ranking. In addition to filling the gap in the literature in terms of the sample consisting of local and global companies, including Türkiye’s pharmaceutical manufacturers, the study is important in terms of the messages the obtained results will give to the sector. Considering operational and environmental efficiency together and including average stock costs, which are among the sectoral problems, in the operational performance indicators increases the originality of the study.